Creative adoption of MS Excel in teaching and learning of chemistry in Malaysia / Lee Sui Chin - Lee, Sui Chin (2013)
This study concerns the creative use of MS Excel in teaching and learning chemistry in Malaysian secondary schools and universities. It is used to explain, explore and understand chemical concepts. Topics such as chemical kinetics, gas compressibility, distribution of molecular speed, period three elements, qualitative analysis, spectroscopy and chemical equilibrium were chosen from Form Six and first/second year university syllabus as examples. For the “qualitative analysis” workbook, a set of videos showing the reactions described are also provided to give the ‘intuitive feel’ of the experiments described in the worksheets. Simple functions in Excel such as ‘Active X’ control tool box, simple macro, chart wizard, hyperlink function and some built in mathematical functions were used extensively in creating the workbooks. These workbooks have provided a stimulative and interesting methodology in learning chemistry. It could offer great benefits to teachers and students in teaching and learning of the said topics. The chemical kinetics workbooks were tried out in secondary schools and the spectroscopy workbook was brought to local universities as field studies. Opinion survey of 612 students from 12 different secondary schools from three states in Malaysia and 68 undergraduate students from various local universities indicated that students were very satisfied with the use of Excel in teaching and learning of chemistry. Data collected were analyzed with descriptive statistics to examine the perception of the respondents and inferential statistics were used to observe the difference in perception between gender and races. The results of the field study showed that most students (>93%) felt that MS Excel program provides a very convenient way for handling experimental kinetic data. It has increased students’ appreciation of chemical kinetics and helped develop their computer skills. The activities provided have exposed students to alternative and more innovative ways of learning chemical kinetics. There is significant difference (p=0.038) in perception between male and female students but no significant difference (p=0.820) in perception among different races. All 24 teachers from 12 schools surveyed also gave very positive comments about this approach. More than 95.0% of the teachers involved in this study found that the MS Excel program is very stimulative and motivated students’ interest in chemistry lessons. They believed that by using this program, thinking process of the students could be further stimulated and improved. Undergraduate students also showed very positive perception towards the spectroscopy workbook. Most (>80%) students agreed that the spectroscopy workbook could help them in learning spectroscopy. However, there is no significant difference (p=0.560) between different gender in their perceptions. This study illustrates how teachers/lecturers can make use of Excel in creating effective and interactive educational environment for teaching and learning chemistry. Workbooks could be created by merely using standard MS Excel program. Simple functions and macros were used to run the task of some buttons created without employing difficult programming or add-ins. With elementary knowledge of Excel, a chemistry teacher would be able to create effective and entertaining teaching aids by using this widely available spreadsheet package in school/university for the benefit of the students.